2021
DOI: 10.3390/horticulturae7010005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Secondary Metabolite Contents and Metabolic Profiles of Six Lycoris Species

Abstract: Quantitative HPLC analysis was performed on six different species of Lycoris herbs to investigate variation in phytochemical content, especially galantamine and phenylpropanoid-derived compounds. The contents of these compounds differed widely among the Lycoris species, with L. radiata and L. chinensis containing the lowest and highest galantamine contents, respectively. Specifically, the galantamine content of L. radiata was 62.5% higher than that of L. chinensis. Following L. radiata, L. sanguinea contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several previous studies have identified and quantified these three flavonoids in medicinal herbs. Yeo et al [29] reported that the epicatechin gallate, quercetin, and kaempferol contents of Lycoris chejuensis were 49 mg, 108 mg, and 38 mg per 1000 g biomass, respectively. In the case of the holly leaf, an herbal medicine, it contains 100 mg of kaempferol per 1000 g biomass [30].…”
Section: Identification Of Major Flavonoid In Orostachys Fimbriata Ex...mentioning
confidence: 99%
“…Several previous studies have identified and quantified these three flavonoids in medicinal herbs. Yeo et al [29] reported that the epicatechin gallate, quercetin, and kaempferol contents of Lycoris chejuensis were 49 mg, 108 mg, and 38 mg per 1000 g biomass, respectively. In the case of the holly leaf, an herbal medicine, it contains 100 mg of kaempferol per 1000 g biomass [30].…”
Section: Identification Of Major Flavonoid In Orostachys Fimbriata Ex...mentioning
confidence: 99%
“…As an important class of bulbous flowers, they also have low environmental requirements and strong adaptability, making them a good choice for landscaping [2]. In addition, the bulbs contain a large number of alkaloid compounds, which have anti-malarial and anti-tumor effects and are a treatment for senile dementia [3,4], so the plants also have important medicinal value. Due to the great ornamental and medicinal value of Lycoris, more and more transcriptomic data have been provided, and functional genes related to excellent breeding traits have been identified [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%